Avoidance of Host Recognition by Alterations in the Repetitive and C-Terminal Regions of AvrXa7, a Type III Effector of Xanthomonas oryzae pv. oryzae - Bing Yang; Akiko Sugio; Frank F. White (Molecular Plant-Microbe Interactions, 2005)
avrXa7 is a member of the avrBs3/pthA gene family. The gene is a critical type III effector in several strains of Xanthomonas oryzae pv. oryzae (virulence activity), and in the presence of the Xa7 host gene for resistance, controls the elicitation of resistance in rice (avirulence activity). The ability of strains containing avrXa7 to adapt to the presence of Xa7 in the host population is dependent, in part, on the genetic plasticity of avrXa7. The potential for the conversion of avrXa7 to a virulence effector without Xa7-dependent elicitor activity was examined. Internal reorganization of avrXa7 by artificially deleting a portion of the central repetitive region resulted in gene pthXo4, which retained virulence activity and lost Xa7-dependent avirulence activity. Similarly, spontaneous rearrangements between repetitive regions of avrXa7 during bacterial culture gave rise to gene pthXo5, which also had virulence activity without Xa7-dependent avirulence activity. pthXo5 appeared to be the result of recombination between avrXa7 and a related gene in the genome. Loss of avirulence activity and retention of virulence activity also resulted from replacement of a portion of the C-terminal coding region of avrXa7 with the corresponding sequence from avrBs3. The results demonstrated the potential for a critical virulence effector to lose avirulence activity while retaining effector function. The results also demonstrated that features of both repetitive and nonrepetitive C-terminal regions of AvrXa7 are involved in avirulence specificity.